Ukrainian women writers and the national imaginary : from the collapse of the USSR to the Euromaidan - Wallo, Oleksandra, 1980- (University of Toronto Press, 2020)
"Since the collapse of the Soviet Union, the Ukrainian literary world has not only experienced a true blossoming of women's prose, but has also witnessed a number of female authors assume the roles of literary trendsetters and authoritative critics of their culture. In this first in-depth study of how Ukrainian women's prose writing was able to re-emerge so powerfully after being marginalized in the Soviet era, Oleksandra Wallo examines the writings and literary careers of leading contemporary Ukrainian women authors, such as Oksana Zabuzhko, Ievheniia Kononenko, and Maria Matios. Her study shows how these women reshaped literary culture with their contributions to the development of the Ukrainian national imaginary in the wake of the Soviet state's disintegration. The interjection of women's voices and perspectives into the narratives about the nation has often permitted these writers to highlight the diversity of the national picture and the complexity of the national story. Utilizing insights from postcolonial and nationalism studies, Wallo's book theorizes the interdependence between the national imaginary and narrative plots, and scrutinizes how prominent Ukrainian women authors experimented with literary form in order to rewrite the story of women and nationhood."-- Provided by publisher
Keywords: Ukrainian prose literature -- Women authors -- History and criticism.; Ukrainian prose literature -- 20th century -- History and criticism.; Ukrainian prose literature -- 21st century -- History and criticism.; Women and literature -- Ukraine -- History.; Nationalism and literature -- Ukraine -- History.; Ukraine -- In literature.; Women in literature.; Prose ukrainienne -- 20e siècle -- Histoire et critique.; Prose ukrainienne -- 21e siècle -- Histoire et critique.; Femmes et littérature -- Ukraine -- Histoire.; Nationalisme et littérature -- Ukraine -- Histoire.; Femmes dans la littérature.; LITERARY CRITICISM -- European -- Eastern.; Literature; Nationalism and literature; Ukrainian prose literature; Women and literature; Women in literature; Ukraine; 1900-2099; Criticism, interpretation, etc.; History